Reviving the Legacy of Islamic Nusantara: A Study of Pegon Script in Traditional Pesantren Communities in Java - Mahfudh, Sahal; El Tiganiy, Abdul Aziz (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
This study aims to explore the dialectics of Pegon script within traditional pesantren communities in Java. Using a sociolinguistic approach, the researcher collected data from seven traditional pesantren communities in Central Java and East Java: PP Roudhotut Tholibin Rembang, PP Roudhotut Thullab Magelang, PP Al Balagh Tuban, PP Fathul Ulum Kediri, LP Al Ma'arif NU Jepara, KOPISODA (Community of KH Sholeh Darat Lovers), and Rifa'iyyah Community Semarang. The findings of this study show that Pegon script in traditional pesantren communities in Java serves several functions, namely: as an identity for traditional pesantren in Java, as a symbol of resistance against colonizers and transnational Islamic movements, as a medium for the transmission of knowledge and the translation of classical Arabic texts, as a gateway for Arabic loanwords into Javanese, and as a preserver of religious traditions and old Javanese language. The preservation pattern of Pegon script in traditional pesantren communities in Java involves producing and disseminating Pegon texts, studying classical Turats using the method of Pegon translation, using Pegon texts as teaching materials, and encouraging community members to write using Pegon script. The motivations for preserving Pegon are as follows: spreading knowledge and preaching, seeking blessings from the righteous, meeting the demands of the community, seeking blessings from the letters of the Qur'an, and economic motivations.